2015
DOI: 10.1111/iwj.12561
|View full text |Cite
|
Sign up to set email alerts
|

The development and testing of a skin tear risk assessment tool

Abstract: The aim of the present study is to develop a reliable and valid skin tear risk assessment tool. The six characteristics identified in a previous case control study as constituting the best risk model for skin tear development were used to construct a risk assessment tool. The ability of the tool to predict skin tear development was then tested in a prospective study. Between August 2012 and September 2013, 1466 tertiary hospital patients were assessed at admission and followed up for 10 days to see if they dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…• skin tears usually occur on fragile exposed skin, often affecting elderly, disabled populations and neonates • evidence of their risk factors is limited and generally dated, and this review aims to give the readers updated information on this issue • physicians and nurses should be aware of the risk factors associated with skin tears in order to minimise risks to patients wherever and whenever possible • prevention should start with early identification of patients at risk of developing skin tears Skin tears may be also very common in public hospital inpatients and residents of aged care facilities, with prevalence of up to 41% in these settings (6,7). Clinical management of skin tears can be difficult, and these wounds may also be associated with prolonged hospitalisation stays, increased health care costs and adverse impacts on patients' quality of life (7,8).…”
Section: Key Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…• skin tears usually occur on fragile exposed skin, often affecting elderly, disabled populations and neonates • evidence of their risk factors is limited and generally dated, and this review aims to give the readers updated information on this issue • physicians and nurses should be aware of the risk factors associated with skin tears in order to minimise risks to patients wherever and whenever possible • prevention should start with early identification of patients at risk of developing skin tears Skin tears may be also very common in public hospital inpatients and residents of aged care facilities, with prevalence of up to 41% in these settings (6,7). Clinical management of skin tears can be difficult, and these wounds may also be associated with prolonged hospitalisation stays, increased health care costs and adverse impacts on patients' quality of life (7,8).…”
Section: Key Messagesmentioning
confidence: 99%
“…Skin tears can be found on all areas of the body and are particularly common on the extremities . Skin tears may be also very common in public hospital inpatients and residents of aged care facilities, with prevalence of up to 41% in these settings .…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the literature identifying individual attributes or clinical characteristics that predicted the risk of skin tears in older adults found that the vast majority of articles were based on lower levels of scientific evidence including expert opinion, case series, and observational studies . Three studies that used advanced statistical modelling to predict the risk of tears were identified . The first study by Lewin et al used multivariate regression analyses of data obtained from a non‐matched case–control study that was conducted in a Western Australian tertiary hospital on participants aged over 50 years .…”
Section: Introductionmentioning
confidence: 99%
“…Secondary analysis was undertaken using stepwise logistic regression of data from the initial case–control study combined with the prospective cohort study, which was subsequently randomly split into two and generated a revised model from one half of the dataset. The revised model reported that senile purpura, haematoma, previously healed skin tears, advanced age, and the ability to reposition independently were better predictors of skin tears . The third study by Sanada et al in 2015 used multiple logistic analyses of data collected from a 3‐month prospective cohort study conducted in Japan and identified that a history of skin tears and a decreased Braden Scale score were significant predictors of skin tears .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation